Warszawska jesień poezji : Konkurs jednego wiersza. (Warszawa : [wydawca nieznany], 1981)
Afisz z wierszami laureatów - Stanisław Soszyński, Zbigniew Atemborski, Barbara Imianowska, Dariusz Tomasz Lebioda, Marek Mystkowski, Krzysztof Kuczkowski.
Keywords: Poezja polska -- 1970-2000.